2007
DOI: 10.1007/s00203-007-0271-4
|View full text |Cite
|
Sign up to set email alerts
|

Diverse rhizobia that nodulate two species of Kummerowia in China

Abstract: A total of 63 bacterial strains were isolated from root nodules of Kummerowia striata and K. stipulacea grown in different geographic regions of China. These bacteria could be divided into fast-growing (FG) rhizobia and slow-growing (SG) rhizobia according to their growth rate. Genetic diversity and taxonomic relationships among these rhizobia were revealed by PCR-based 16 S rDNA RFLP and sequencing, 16 S-IGS RFLP, SDS-PAGE of whole cell soluble proteins, BOX-PCR and symbiotic gene (nifH/nodC) analyses. The sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
8
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 60 publications
1
8
0
Order By: Relevance
“…The microsymbionts associated with Dalbergia species in Chinese soils have not been studied. In this study, a group of Dalbergia rhizobia are reported that showed close phylogenetic relationships with some strains isolated from Albizia (Wang et al, 2006) and Kummerowia (Lin et al, 2007), also grown in subtropical regions. Based upon a comparative study with multiple analyses, these strains were classified into a single group distinct from defined Rhizobium species.…”
mentioning
confidence: 56%
See 1 more Smart Citation
“…The microsymbionts associated with Dalbergia species in Chinese soils have not been studied. In this study, a group of Dalbergia rhizobia are reported that showed close phylogenetic relationships with some strains isolated from Albizia (Wang et al, 2006) and Kummerowia (Lin et al, 2007), also grown in subtropical regions. Based upon a comparative study with multiple analyses, these strains were classified into a single group distinct from defined Rhizobium species.…”
mentioning
confidence: 56%
“…Kummerowia species are leguminous plants of medicinal value that originate from East Asia, and some of them have been introduced to other areas. Our previous data indicated that Kummerowia species were non-selective hosts for rhizobia and that they might nodulate with various bacteria in different regions (Lin et al, 2007(Lin et al, , 2008. Rosewoods (species of Dalbergia L.), belonging to the subfamily Papilionoideae of the Leguminosae, are slowgrowing ornamental trees, some of which have medicinal value (Ito et al, 2003), and are usually used as hard timber in furniture production.…”
mentioning
confidence: 99%
“…They also hypothesized that the environment selects is, in part, responsible for spatial variation in microbial diversity. Some previous studies have demonstrated that biogeographic patterns also exist in rhizobia, the symbiotic bacteria [22,26,27] . The data in the present study and in the previous studies showed that the geological distribution of nodule occupant bacteria or symbiotic bacteria in root and/or stem nodules were not only determined by the environment, but also related to the geography of their corresponding host plants.…”
Section: Discussionmentioning
confidence: 98%
“…S3), which was consistent with the phylogenetic relationships estimated from 16S rRNA gene sequences. Since the similarity of protein patterns among strains within a rhizobial species is always greater than 80 % (Gu et al, 2007;Lin et al, 2007;Liu et al, 2007;Yan et al, 2007), the results of this analysis also imply that the two Tibetan strains represent a species that is distinct from the Rhizobium species represented by the reference strains.…”
mentioning
confidence: 88%